Persepsi Orang Tua tentang Dampak Penggunaan Media Sosial Pada Remaja - Grace Fresania Kaparang; Nova Gerungan; Indriany Lestari Pangulimang (Ideas Publishing, 2022)
The purpose of this study was to find out an overview of parents perceptions of the impact of social media use on adolescents with a total sample of 35 from purposive sampling techniques and analytical descriptive research methods. The measuring instrument used is a questionnaire of parents perceptions of social media. The results of the study stated that the majority of participants had internet access, but not all were registered on social media networks. It was also found that all participating children were registered on one of the social media networks and the majority of parents supported the child being registered on one of the social media. The majority of participants said they could stop their children from using social media, and all participants were aware of threats on social media. Realizing this, the majority of parents discussed social media threats with their children and the most preferred security measure by the majority of participants was with parental monitoring measures. According to participants, the most responsible for protecting children are parents, but the rest also argue that teachers, schools, internet service providers and mass media have a responsibility. Parents are expected to always monitor children in the use of social media because from the results it is found that parents actually have authority in regulating childrens social media use.